1988
DOI: 10.1099/00222615-26-3-199
|View full text |Cite
|
Sign up to set email alerts
|

Site of action of a gonococcal growth inhibitor produced by Staphylococcus haemolyticus

Abstract: Summary. The inhibitory substance produced by Staphylococcus haemolyticus strain no. 7 acts on growing as well as resting gonococcal cells, as shown by reductions in viable counts. The optical density of these cell suspensions was only slightly reduced. The inhibitor caused lysis of gonococcal spheroplasts at 24°C and 37"C, but was much less active at 4°C. Acting on intact gonococcal cells, the inhibitor caused a temperature-dependent release of radioactive cytoplasmic material. Electronmicroscopy showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
(1 reference statement)
0
7
0
Order By: Relevance
“…Among the sarZ downregulated genes, we detected 1 gene whose expression was increased ϳ2-3-fold in the sarZ mutant. This gene had similarities to hemolysins, such as the S. lugdunensis slush peptides [41] and the gononococcal growth inhibitor peptide AGS of S. haemolyticus [42]. Interestingly, the sarZ mutant exhibited pronounced ␤ hemolysis on sheep agar plates, a phenotype known from the synergistic activities of ␦-toxin and either ␣-or ␤-toxin in S. aureus [43], but not commonly seen in S. epidermidis ( figure 4C), which indicates that sarZ regulates hemolysis, possibly by an effect on the gene SERP2258.…”
Section: Resultsmentioning
confidence: 99%
“…Among the sarZ downregulated genes, we detected 1 gene whose expression was increased ϳ2-3-fold in the sarZ mutant. This gene had similarities to hemolysins, such as the S. lugdunensis slush peptides [41] and the gononococcal growth inhibitor peptide AGS of S. haemolyticus [42]. Interestingly, the sarZ mutant exhibited pronounced ␤ hemolysis on sheep agar plates, a phenotype known from the synergistic activities of ␦-toxin and either ␣-or ␤-toxin in S. aureus [43], but not commonly seen in S. epidermidis ( figure 4C), which indicates that sarZ regulates hemolysis, possibly by an effect on the gene SERP2258.…”
Section: Resultsmentioning
confidence: 99%
“…Some peptides that were described before the term PSM was coined are now known to belong to the PSM family, such as the PSMβ-like SLUSH peptides from Staphylococcus lugdunensis or the gonococcal growth inhibitor (GGI) peptides from Staphylococcus haemolyticus (Donvito et al, 1997; Frenette et al, 1984). Analysis of the culture filtrates of a series of staphylococcal species by reversed-phase high-pressure chromatography/mass spectrometry (RP-HPLC/MS), which is the optimal method to measure PSM production, showed that many staphylococci produce PSMs (Rautenberg et al, 2011).…”
Section: Psms Are Widespread In Staphylococcimentioning
confidence: 99%
“…Moreover, they are also different from the amino acid sequence of 6-lysin of S. aureus reported by Fitton et al (1980) even though many properties are shared by these substances. Frenette et al (1984) have shown that the antigonococcal substance and 8-lysin have similar haemolytic spectra, affinity for some phospholipids, the absence of proline, tyrosine, histidine, arginine and cysteine from their amino acid compositions, a high predominance of hydrophobic residues and the ability to disrupt tissueculture cells. However, on the basis of the limited amino acid sequence homology between these substances, the peptides I, II and III cannot be considered as another class of 8-haemolysin, as is the case for dog 8-lysin (Fitton et al, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…7 was used for the production of the bactericidal inhibitor (Bisaillon et al, 1980;Lafond et al, 1981;Beaudet et al, 1982). The reference target strain was Neisseria gonorrhoeae G-10 and it was cultivated as previously described (Frenette et al, 1984). These strains were kept either in a freeze-dried state or as frozen suspensions at -76°C.…”
Section: Materials and Methods Bacterial Strainsmentioning
confidence: 99%
See 1 more Smart Citation